Rulisca: Science learning media for elementary school students - Ari Suryawan; Evalina Evalina; Novi Wulandani (Universitas Muhammadiyah Magelang, 2024)
A crucial responsibility of teachers lies in fostering innovative learning processes. Meaningful learning experiences facilitate students' comprehension of the subject matter. Consequently, the need arises for instructional media to serve as teaching aids, cultivating an engaging learning environment for students. The core concept of instructional media lies in facilitating students' understanding from abstract to concrete concepts. Its primary functions include serving as a learning resource, providing information and knowledge to students. Furthermore, instructional media can motivate learning, reinforce previously learned material, and stimulate students. One such innovative tool is the